CHILDREN AS VICTIMS OF WAR IN BAHMAN GHOBADI’S TURTLES CAN FLY MOVIE (2005): A SOCIOLOGICAL APPROACH - HANDAYANI, SUYEKTI NUR (2011)
reflected in Bahman Ghobadi’s Turtles Can Fly Movie . The objectives of the study are to analyze the structural elements of the movie and to analyze the movie based on the sociological perspective. This study employs the qualitative method. The object of the study is Turtles Can Fly movie directed by Bahman Ghobadi. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the movie itself and the secondary data are script text and some references related to the research. The techniques of data collection are note-taking and image-capturing. The technique of data analysis is descriptive analysis. The results of the research shows the following conclusions. Firstly, based on the structural analysis, it shows that narrative and the technical elements of Turtles Can Fly movie are related to each other and form the unity into good quality of a movie. Secondly, based on the sociological analysis, there is close relation between movie production and the historical background in Iraq that lead by Saddam Hussein and under chaos of Iraq war. And the issue is about children who as victim of war.